Production process of cyclically regenerated polylactic acid and low-temperature spandex fabric

By recycling and processing textiles, using catalysts and low-temperature dyeing processes, the problem of poor regeneration and dyeing effects in the prior art is solved, efficient fabric recycling and reuse is achieved, and the mechanical properties and dyeing effects of the fabric are improved.

CN119615411AActive Publication Date: 2025-03-14SHENZHEN NAERSI FASHION CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411789259.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-03-14
Estimated Expiration
2044-12-06

AI Technical Summary

Technical Problem

In the prior art, when recycling textiles, it is difficult to effectively improve the regeneration performance and dyeing effect of the fabric. At the same time, high-temperature treatment will damage the structure of spandex and polylactic acid, resulting in a decrease in elasticity and increased stress of the fabric.

Method used

By recycling polylactic fiber, cotton fiber, polyester fiber and spandex fabrics, using organic solvents and phosphoric acid solutions, and preparing PLA decomposition catalyst and lactide ring opening catalyst, the raw materials are processed, combined with a low-temperature dyeing process, vitamin B12, chain extenders and isocyanate are added to improve the mechanical properties and dyeing effect of the fabric.

Benefits of technology

The stress reduction, dyeing and color fixing effect of regenerated polylactic acid and low-temperature spandex fabrics has been achieved, and the closed loop of recycling and reuse of polylactic acid and spandex waste fabrics has been achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119615411A_ABST
    Figure CN119615411A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of fabric recovery, in particular to a production process of cyclically regenerated polylactic acid and low-temperature spandex fabric. The production process provided by the invention overcomes the problems of high stress of polylactic acid and low-temperature spandex fabrics at low temperature and poor dyeing and fixation effects. Four different types of fabrics including polylactic acid fibers, cotton fibers, polyester fibers and spandex are subjected to recovery treatment and physical treatment and then treated with an organic solvent and a phosphoric acid solution, and the raw materials are treated with a prepared PLA decomposition catalyst and a lactide ring-opening catalyst. Vitamin B12, a chain extender and isocyanate are supplemented in the technological process, and the dyeing process of low-temperature treatment is adopted, so that the stress of the regenerated polylactic acid and low-temperature spandex fabric is reduced, the dyeing and color fixing effects are good, and the closed loop of recycling and reusing of the polylactic acid and spandex waste fabric is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of textile recycling, in particular to a production process for recycled polylactic acid and low-temperature spandex fabrics. Background Art

[0002] Spandex fiber and polylactic acid fiber processing technology is an important part of the current textile industry. With the introduction of the concept of "recovery, reconstruction and regeneration" of the circular economy, the recycling of textile waste has become a research hotspot in the textile industry. How to improve the reuse of recycled materials, reduce production costs and ensure the basic performance of recycled fabrics has become a hot research issue. Polylactic acid, as a polymer material, is green, pollution-free and degradable. Polylactic acid is widely used in fabrics and mixed with other types of raw materials to improve the softness and breathability of the fabric. Spandex materials are used in blended fabrics to improve the elasticity of the material and are also widely used.

[0003] As of August 2024, the import volume of polylactic acid is 30,833.4 tons, up 48.8% from the same period last year. On the one hand, polylactic acid relies on imports, and on the other hand, there are still a large number of polylactic acid textile waste in the textile field. The conflict between them has prompted people to recycle textile waste. Among the existing technologies, there are two main ways to treat recycled fabrics. One is to treat the fabrics by physical and mechanical treatment, but it is of no benefit to the regeneration and performance improvement of the fabrics, and the recovery rate is low. The other is to treat the recycled fabrics by chemical modification, which can maximize the high utilization and regeneration of the fabrics.

[0004] However, in the process of chemical modification, the modified fabric has poor dye fixation effect on the dye, and the fabric cannot withstand the high temperature treatment steps in the dyeing process. For example, the conventional dyeing treatment of spandex fabrics requires a high temperature of 160°C or above, but it damages the spandex structure, reduces the elasticity of the spandex fabric, increases stress, and reduces the comfort of human wearing; in the case of blending with polylactic acid, polylactic acid begins to degrade at 120-130°C, and the treatment temperature of the prior art has an adverse effect on both spandex and polylactic acid. However, without high-temperature treatment, the low-temperature spandex fabric obtained by the low-temperature process has poor dyeing effect and poor color fixation effect, and the fabric is easy to decolorize. At the same time, polylactic acid is often mixed with cotton fiber in the recycled fabric. Pure cotton fiber is highly comfortable, but difficult to decompose. After mixing with polylactic acid, the biodegradability of cotton fiber is improved. Therefore, it is imperative to effectively utilize the plant fiber in cotton fiber.

[0005] Therefore, a production process of recycled polylactic acid and low-temperature spandex fabric is proposed. Summary of the invention

[0006] The purpose of the present invention is to provide a production process for recycled polylactic acid and low-temperature spandex fabrics. Four different types of fabrics, polylactic acid fiber, cotton fiber, polyester fiber and spandex, are recycled and treated with organic solvents and phosphoric acid solutions after physical treatment. The raw materials are treated by using prepared PLA decomposition catalysts and lactide ring-opening catalysts. Vitamin B12, chain extenders and isocyanates are added during the process, and a low-temperature treatment dyeing process is adopted, so that the stress of the recycled polylactic acid and low-temperature spandex fabrics is reduced, the dyeing and fixing effects are good, and a closed loop of recycling and reuse of polylactic acid and spandex waste fabrics is realized.

[0007] To achieve the above object, the present invention provides the following technical solutions:

[0008] The present invention provides a production process of recycled polylactic acid and low-temperature spandex fabric, and the production process is as follows:

[0009] S1 fabric recycling;

[0010] S2, by weight, 20 parts of the crushed fabric and 760-1300 parts of a mixed solvent are mixed at 40-55° C., and a phosphoric acid aqueous solution with a mass fraction of 78%-86% is added to react to obtain a dissolving solution; the mixed solvent is composed of water and dimethylacetamide in a ratio of 2-13:3-11;

[0011] S3: adding 0.1-0.4 parts of PLA decomposition catalyst to the dissolving solution, and irradiating with ultraviolet light for 80-102 hours to obtain decomposition solution 1; dissolving 10-12 parts of lactide in 100 parts of dimethylacetamide to obtain a lactide solution; and adding the lactide solution to the decomposition solution 1 to obtain a decomposition solution 2;

[0012] S4 removes water from the decomposition liquid 2 to obtain a treated decomposition liquid 2; mixes the treated decomposition liquid 2 with 5 parts of epoxy compound and 0.01-0.03 parts of lactide ring-opening catalyst, reacts at 135-170° C. under vacuum conditions for 15-25 minutes, and cools to obtain a decomposition liquid 3;

[0013] S5: adding 4-7 parts of nanocellulose and 2-5 parts of the composition to the decomposition liquid 3, and then adding 0.01-0.03 parts of a lactide ring-opening catalyst, reacting at 115-125° C. under vacuum conditions for 60-85 minutes to obtain a melt; the ratio of vitamin B12, triethanolamine and isocyanate in the composition is 6-7:2-3:1-2;

[0014] S6: the material to be melted is mixed with wheat starch and then melted at 140-170°C, and the yarn is spun; 1 / 3-1 / 4 processing aid is added to the yarn, and after weaving, the yarn is immersed in the dye solution for programmed heating, heat preservation and cooling; wherein the second and third programmed heating rates are both 1.3-1.7°C / min; the third programmed heating temperature is 115-130°C; the first programmed cooling temperature is 1.6-2.0°C / min.

[0015] Preferably, the production process of the PLA decomposition catalyst in S3 is as follows: 15 parts of tetrabutyl titanate are dissolved in anhydrous ethanol to obtain a tetrabutyl titanate solution; the ratio of tetrabutyl titanate to anhydrous ethanol is 1:30; 7 parts of polyethylene glycol with a polymerization degree of 5, 4 parts of nitric acid and 8 parts of water are mixed to obtain a reaction solution 1; 0.10-0.18 parts of α-ferric oxide and 0.05-0.10 parts of tungsten dioxide are added to anhydrous ethanol in a mortar in small amounts and multiple times to grind to obtain a reaction solution 2; the amount of anhydrous ethanol used is 10 parts; after adding the reaction solution 2 to the tetrabutyl titanate solution and stirring, the reaction solution 1 is added, stirred at 30°C for 24 hours, dried and ground to obtain a calcined material; the calcined material is put into a tubular furnace, roasted at 450°C for 5 hours, and cooled to obtain a PLA decomposition catalyst.

[0016] Preferably, the preparation method of the lactide ring-opening catalyst in S4 is as follows: dissolving 2.8-3.0 parts of 1-(chloro-1-pyrrolidinyl methylene) pyrrolidine tetrafluoroborate in 20 parts of acetonitrile to obtain a 1-(chloro-1-pyrrolidinyl methylene) pyrrolidine tetrafluoroborate solution; dissolving 0.9 parts of 1,2-cyclohexanediamine and 2.1 parts of triethylamine in 20 parts of acetonitrile to obtain a mixed solution; slowly adding the 1-(chloro-1-pyrrolidinyl methylene) pyrrolidine tetrafluoroborate solution dropwise to the mixed solution at 0°C, heating to 85°C, reflux stirring for 12 hours, and then adding 1.7 parts of sodium hydroxide to obtain a lactide ring-opening catalyst precursor; drying the lactide ring-opening catalyst precursor under vacuum to remove the organic solvent and triethylamine, then adding 2.3 parts of potassium hydroxide, stirring, extracting with acetonitrile, removing water with anhydrous sodium acetate, and then distilling under reduced pressure to obtain a lactide ring-opening catalyst intermediate;

[0017] Dissolve 0.1-0.2 parts of zinc trifluoromethanesulfonate in 5 parts of tetrahydrofuran to obtain a zinc trifluoromethanesulfonate solution; dissolve 0.3 parts of a lactide ring-opening catalyst intermediate in 10 parts of tetrahydrofuran to obtain a lactide ring-opening catalyst intermediate solution; raise the temperature of the lactide ring-opening catalyst intermediate solution to 60° C.; drop the lactide ring-opening catalyst intermediate solution into the zinc trifluoromethanesulfonate solution, filter the obtained precipitate, wash it with tetrahydrofuran and ether, and then dry it to obtain a lactide ring-opening catalyst.

[0018] Preferably, the process steps of fabric recycling treatment of S1 are as follows: first, textile fabrics are selected, and textile fabrics that do not meet the requirements are eliminated, including dark-colored fabrics, fabrics with pungent odors, and fabrics with high additive content. The retained fabrics are mixed fabrics of polylactic acid fiber, cotton fiber, polyester fiber and spandex; the mass ratio of polylactic acid fiber, cotton fiber, polyester fiber and spandex in the mixed fabric is 58:34:3:5; the mixed fabric is washed with clean water and then dried, then shredded, and crushed with a pulverizer and opened to obtain pulverized fabric.

[0019] Preferably, the epoxy compound is one of cyclohexene oxide, ethylene oxide, hydroxyethyl methacrylate and epoxyisoquinoline.

[0020] Preferably, the temperature of the vacuum condition in S4 is 135-150° C.; and the amount of the lactide ring-opening catalyst used in S4 and S5 is 0.01-0.02 parts.

[0021] Preferably, the isocyanate is one of 1,3-bis(1-isocyanato-1-methylethyl)benzene, 4,4'-methylenebis(phenyl isocyanate), toluene-2,4-diisocyanate and isophorone diisocyanate.

[0022] Preferably, the processing aid contains a humectant; the humectant consists of betaine and anionic surfactant; the ratio of betaine to anionic surfactant is 1:1-2; and the anionic surfactant is one of sodium cocoyl glycinate and sodium lauroyl glutamate.

[0023] Preferably, the processing aid contains a dyeing aid; the dyeing aid is one of sodium docusate, sodium diisobutyl sulfosuccinate and disodium monoisodecyl sulfosuccinate.

[0024] Preferably, the ratio of the moisturizer, the dyeing aid and the desizing agent in the processing aid is 3-5:2-5:2-3; the finishing agent is added after the first program cooling in S6; the ratio of the ester quaternary ammonium salt, chitosan and silicone polyoxyethylene ether in the finishing agent is 1-3:2:1-5.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] 1. Four different types of fabrics, namely polylactic acid fiber, cotton fiber, polyester fiber and spandex, are recycled, physically cut and crushed, and then subjected to solvent treatment using a mixed solvent. The ratio of water and organic solvent in the mixed solvent is adjusted, the heating mixing temperature is controlled, and then a phosphoric acid aqueous solution is added for treatment to dissolve the mixed fabric to obtain a solution, thereby promoting the chemical modification, and the mechanical properties of the recycled polylactic acid and low-temperature spandex fabrics are improved.

[0027] 2. PLA decomposition catalyst is prepared, and the catalyst is tungsten dioxide and α-Fe2O3 loaded with titanium dioxide, which can effectively decompose polylactic acid fiber into lactide. The obtained PLA decomposition catalyst has photocatalytic effect, generates electron-hole pairs under ultraviolet light irradiation, and promotes the decomposition of the polylactic acid structure by the loaded α-Fe2O3. By optimizing the production process of PLA decomposition catalyst, reasonably adjusting the amount of PLA decomposition catalyst in the system, changing the ultraviolet irradiation time, and reasonably adjusting the proportion of added lactide, nanocellulose and the composition, on the one hand, the effect of supplementing the components in the original crushed fabric is achieved, and on the other hand, the polymerization and reaction of the above components are promoted, further improving the fracture strength of recycled polylactic acid and low-temperature spandex fabric, reducing stress, having good dimensional stability, not easy to shrink, and realizing the closed loop of recycling polylactic acid and spandex.

[0028] 3. By synthesizing a lactide ring-opening catalyst and controlling the dosage of the reaction raw materials 1-(chloro-1-pyrrolidinylmethylene) pyrrolidine tetrafluoroborate and zinc trifluoromethanesulfonate, the catalyst obtained has high activity for the ring-opening and polymerization of lactide. By adjusting the dosage of the lactide ring-opening catalyst in the decomposition liquid 2 and the decomposition liquid 3, and adjusting the reaction temperature and time of the decomposition liquid, the ring-opened lactide polymerizes to form polylactic acid, or polymerizes with the added isocyanate, nanocellulose, and polyterephthalic acid obtained by decomposition of polyester, thereby improving the temperature resistance of the recycled polylactic acid and the low-temperature spandex fabric.

[0029] 4. By adding vitamin B12, chain extender and isocyanate to S5, and reacting with the spandex decomposition product in decomposition liquid 3, spandex material is obtained. The proportion of isocyanate is reasonably adjusted, and vitamin B12 is creatively added. The hydroxyl group of vitamin B12 reacts with isocyanate, and a tertiary amine structure compound is introduced. As a nucleophilic reagent, it provides electrons to cationic dyes and promotes the binding force between cationic dyes and fabrics. By adding moisturizers, dyeing aids and desizing agents, and reasonably adjusting the types and amounts, the dyeing rate and color fastness of the fabric are improved.

[0030] 5. By adjusting the melting temperature, spinning, adding some processing aids to the spinning, and then dyeing, adjusting the heating rate and the temperature maintained during the dyeing process, adopting a low-temperature production process, and adjusting the cooling rate, and adding the remaining processing aids after soaking in water, and finally adding the finishing agent and adjusting the proportion of the finishing agent, the structure and properties of the components in the fabric are retained to the greatest extent, and the fabric has a high dyeing rate and color fastness. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 It is a graph showing the dyeing rate and color fastness results of Examples 36, 39-50 of the present invention and Comparative Examples 16-20. DETAILED DESCRIPTION

[0032] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0033] See also Figure 1 The present invention provides a production process of recycled polylactic acid and low-temperature spandex fabrics, and the technical solution is as follows:

[0034] The substance information involved in the present invention is as follows:

[0035] Toluene-2,4-diisocyanate CAS: 584-84-9; Dimethylacetamide CAS: 127-19-5; Lactide CAS: 95-96-5; Vitamin B12 CAS: 68-19-9; Triethanolamine CAS: 102-71-6; Betaine CAS: 107-43-7; Sodium cocoyl glycinate CAS: 90387-74-9; Sodium docusate CAS: 577-11-7; Ester quaternary ammonium salt CAS: 91995-81-2; Chitosan CAS: 1398-61-4; Silicone polyoxyethylene ether CAS: 68937-54-2; 1-(chloro-1-pyrrolidinyl methylene) pyrrolidine tetrafluoroborate CAS: 115007-14-2; 1,2-cyclohexanediamine CAS: 694-83-7; Zinc trifluoromethanesulfonate CAS: 54010-75-2; Cyclohexene oxide CAS: 286-2 0-4; Ethylene oxide CAS: 75-21-8; Hydroxyethyl methacrylate CAS: 868-77-9; Epoxyisoquinoline CAS: 140468-94-6; Zinc 2-ethylhexanoate CAS: 136-53-8; 1,3-Bis(1-isocyanato-1-methylethyl)benzene CAS: 2778-42-9; 4,4'-Methylenebis(phenyl isocyanate) CAS: 101-68-8; Isophorone diisocyanate CAS: 4098-71-9; Sodium lauroyl glutamate CAS: 29923-31-7; Sodium diisobutyl sulfosuccinate CAS: 127-39-9; Disodium monoisodecyl sulfosuccinate CAS: 37294-49-8.

[0036] Example 1

[0037] S1 Fabric recycling: First, textile fabrics are selected and those that do not meet the requirements are eliminated, including dark-colored fabrics, fabrics with pungent odors, and fabrics with high additive content. The retained fabrics are mixed fabrics of polylactic acid fiber, cotton fiber, polyester fiber, and spandex; the mass ratio of polylactic acid fiber, cotton fiber, polyester fiber, and spandex in the mixed fabric is 58:34:3:5; the mixed fabric is washed with clean water and dried, then cut into pieces, and crushed with a pulverizer to obtain crushed fabric;

[0038] S2: 20 parts of crushed fabric and 1000 parts of mixed solvent were mixed at 40°C, mechanically stirred at 500 rpm for 2 hours, and then 500 parts of 83% phosphoric acid aqueous solution preheated to 40°C (the preheating temperature and the mixing temperature were kept consistent), and the stirring was continued for 4 hours. The liquid obtained by filtration was the dissolving liquid; the mixed solvent was composed of water and dimethylacetamide, and the mass ratio of the two was 11:9;

[0039] S3: adding 0.4 parts of PLA decomposition catalyst to the dissolving liquid and stirring evenly, irradiating under a 25W ultraviolet lamp at a rotation speed of 300rpm, with an ultraviolet wavelength of 254nm, until the content of lactide monomer no longer changes, irradiating for 80h to obtain decomposition liquid 1; dissolving 12 parts of lactide in 100 parts of dimethylacetamide to obtain a lactide solution; and mixing the lactide solution and decomposition liquid 1 evenly to obtain decomposition liquid 2;

[0040] S4: removing moisture from the decomposition liquid 2 by using anhydrous sodium sulfate to obtain a treated decomposition liquid 2; mixing the treated decomposition liquid 2 with 5 parts of epoxy compound and 0.02 parts of lactide ring-opening catalyst, reacting the mixture under vacuum conditions at 150° C. for 20 minutes, and cooling the mixture to obtain a decomposition liquid 3;

[0041] S5: adding 7 parts of nanocellulose (derived from cotton fiber) and 4 parts of the composition to the decomposition liquid 3, and then adding 0.1 parts of dibutyltin dilaurate and 0.01 parts of lactide ring-opening catalyst, reacting at 125°C under vacuum conditions for 60 minutes, cooling and vacuum drying to remove the organic solvent, to obtain a melt; the ratio of vitamin B12, chain extender (triethanolamine) and isocyanate in the composition is 7:2:1;

[0042] S6: The melt to be melted is mixed with 0.5 parts of wheat starch and then melted at 160°C, and then spun at a speed of 500m / min, and then stretched, oiled and wound to obtain yarn; the size of the fiber in the yarn is 4.4tex (40D), 2 / 3 (mass ratio) of processing aids are added to the yarn, and then the recycled polylactic acid and low-temperature spandex fabric precursor are woven; the ratio of the melt to the total processing aids is 200:1; the ratio of betaine and sodium cocoyl glycinate (humectant), sodium docusate (dyeing aid) and sodium carbonate (desizing agent) in the processing aids is 5:2:3; the cationic dye and water are mixed at a mass ratio of 1:100 to obtain a dye solution; the low-temperature spandex fabric precursor is immersed in the dye solution for 10 minutes, and then the dye solution is heated at 2.0℃ / m in for the first time to reach 80°C, after holding for 6 minutes, the second time to reach 100°C at a rate of 1.5°C / min, after holding for 8 minutes, the third time to reach 120°C at a rate of 1.5°C / min, after holding for 25 minutes, the first time to cool at a rate of 1.8°C / min, after the temperature reaches 60°C, it is put into water for 5 minutes, 1 / 3 of the processing aid is added to the water, and then the third time to reach 70°C is heated at a rate of 1.5°C / min, the temperature is maintained for 20 minutes, then cooled and dried to obtain recycled polylactic acid and low-temperature spandex fabrics; the mass ratio of the melt to the finishing agent is 500:1; the mass ratio of ester quaternary ammonium salt, chitin and silicone polyoxyethylene ether in the finishing agent is 1:2:1.

[0043] The production process of S31 PLA decomposition catalyst is as follows: 15 parts of tetrabutyl titanate are dissolved in anhydrous ethanol to obtain a tetrabutyl titanate solution; the ratio of tetrabutyl titanate to anhydrous ethanol is 1:30; 7 parts of polyethylene glycol with a polymerization degree of 5, 4 parts of nitric acid and 8 parts of water are mixed to obtain a reaction solution 1; 0.15 parts of α-ferric oxide and 0.05 parts of tungsten dioxide are ground in a mortar with anhydrous ethanol in small amounts for multiple times to obtain a reaction solution 2, and the amount of anhydrous ethanol used is 10 parts; after adding the reaction solution 2 to the tetrabutyl titanate solution and stirring, the reaction solution 1 is added, stirred at 30°C for 24 hours, dried and ground to obtain a calcined material; the calcined material is put into a tubular furnace, roasted at 450°C for 5 hours, and cooled to obtain a PLA decomposition catalyst;

[0044] The preparation method of S41 lactide ring-opening catalyst is as follows: 2.8 parts of 1-(chloro-1-pyrrolidinyl methylene) pyrrolidine tetrafluoroborate are dissolved in 20 parts of acetonitrile to obtain a 1-(chloro-1-pyrrolidinyl methylene) pyrrolidine tetrafluoroborate solution; 0.9 parts of 1,2-cyclohexanediamine and 2.1 parts of triethylamine are dissolved in 20 parts of acetonitrile to obtain a mixed solution; the 1-(chloro-1-pyrrolidinyl methylene) pyrrolidine tetrafluoroborate solution is slowly added dropwise to the mixed solution at 0°C, the temperature is raised to 85°C, refluxed and stirred for 12 hours, and then 1.7 parts of sodium hydroxide are added to obtain a lactide ring-opening catalyst precursor; the lactide ring-opening catalyst precursor is dried under vacuum to remove the organic solvent and triethylamine, and then 2.3 parts of potassium hydroxide are added, and after stirring, acetonitrile is used to extract, and anhydrous sodium acetate is used to remove water and then distilled under reduced pressure to obtain a lactide ring-opening catalyst intermediate;

[0045] 0.2 parts of zinc trifluoromethanesulfonate are dissolved in 5 parts of tetrahydrofuran to obtain a zinc trifluoromethanesulfonate solution; 0.3 parts of a lactide ring-opening catalyst intermediate are dissolved in 10 parts of tetrahydrofuran to obtain a lactide ring-opening catalyst intermediate solution; the temperature of the above solution is raised to 60° C., the lactide ring-opening catalyst intermediate solution is dropped into the zinc trifluoromethanesulfonate solution, the obtained precipitate is filtered, washed with tetrahydrofuran and ether, and then dried to obtain a lactide ring-opening catalyst.

[0046] Example 2-12

[0047] Different from Example 1, the production process conditions of S2 are changed, as shown in Table 1.

[0048] Table 1 Production process conditions of the solution in S2

[0049]

[0050] Comparative Example 1

[0051] The difference from Example 1 is that the amount of the mixed solvent is 500 parts.

[0052] Comparative Example 2

[0053] Different from Example 1, the mixing temperature was 25°C.

[0054] Comparative Example 3

[0055] Different from Example 1, the mixing temperature is 70°C.

[0056] Comparative Example 4

[0057] The difference from Example 1 is that the mass percentage of the phosphoric acid aqueous solution is 90%.

[0058] Comparative Example 5

[0059] The difference from Example 1 is that the ratio of water to dimethylacetamide is 1:3.

[0060] Embodiment 13

[0061] The recycled polylactic acid obtained in Examples 1-12 and Comparative Examples 1-5 was tested for stress relief rate and breaking strength with low-temperature spandex fabrics. The stress relief rate test method is as follows: S1 Fabric recycling: First, the textile fabrics are selected, and the textile fabrics that do not meet the requirements are eliminated. The eliminated fabrics include dark-colored fabrics, fabrics with pungent odors, and fabrics with high additive content. The retained fabrics are mixed fabrics of polylactic acid fiber, cotton fiber, polyester fiber and spandex; the mass ratio of polylactic acid fiber, cotton fiber, polyester fiber and spandex in the mixed fabric is 58:34:3:5; the mixed fabric is washed with clean water and dried, then shredded, and crushed with a pulverizer and then loosened to obtain a pulverized fabric; S2 The pulverized fabric and dimethylacetamide are mixed in a mass ratio of 1:10 and spun, and then the S6 step in Example 1 is performed. The stress measured on the produced fabric is recorded as A, and the stress measured in the embodiment and the comparative example is recorded as B. The calculation formula for the stress relief rate is as follows: The test results are shown in Table 2.

[0062] Table 2 Stress relief rate and breaking strength test results of Examples 1-12 and Comparative Examples 1-5

[0063] 300% stress relief rate (%) Breaking strength(g) Example 1 93.8 96.9 Example 2 93.0 96.1 Example 3 92.8 95.3 Example 4 93.7 97.0 Example 5 94.0 97.3 Example 6 93.8 96.7 Example 7 93.1 96.2 Example 8 94.5 98.3 Example 9 94.0 97.6 Example 10 95.1 100.1 Embodiment 11 93.5 96.8 Example 12 91.0 93.2 Comparative Example 1 51.1 89.5 Comparative Example 2 72.5 91.8 Comparative Example 3 80.0 94.0 Comparative Example 4 49.3 86.5 Comparative Example 5 38.0 75.4

[0064] As shown in Tables 1 and 2, the recycled polylactic acid and low-temperature spandex fabrics produced by the present invention have a 300% stress relief rate of 91.0%-95.1% and a breaking strength of 93.2-100.1g. Four different types of fabrics, polylactic acid fiber, cotton fiber, polyester fiber and spandex, are dissolved by using a mixed solvent composed of water and dimethylacetyl, wherein water preliminarily dissolves the plant fiber in the cotton fiber, dimethylacetyl preliminarily dissolves the polylactic acid fiber, cotton fiber and spandex, and the material is deeply dissolved under the action of heating and phosphoric acid. The results of Examples 1-4 show that as the amount of mixed solvent increases, the 300% stress relief rate and breaking strength increase and then tend to stabilize. When the mixed solvent is mixed with the crushed fabric, the amount of the mixed solvent should at least cover the volume of the crushed fabric. As the mixed solvent increases, the amount of dissolved components of the fabric components in the mixed solvent increases, which helps the subsequent chemical modification process. However, when the amount is too high, as shown in Example 4, since the amount of crushed fabric is fixed, the amount dissolved in the mixed solvent is constant, and the stress relief rate and breaking strength of the produced recycled polylactic acid and low-temperature spandex fabrics are no longer improved; as shown in Comparative Example 1, due to the small amount of mixed solvent, the content of dissolved fabric components is lower than that of Examples 1-4, so the performance of the fabric is reduced. The results of Examples 1, 5 and 6 show that when the mixing temperature is 45°C, the solubility of the fabric components in the mixed solvent is the best, so the performance of the produced fabric is the best. If the temperature is too high or too low, as shown in Comparative Examples 3 and 2, it will have a bad effect on the recycled polylactic acid and low-temperature spandex fabrics. The results of Examples 5, 7-9 show that as the mass percentage of phosphoric acid aqueous solution increases, the 300% stress relief rate and breaking strength show a trend of first increasing and then decreasing. Phosphoric acid can cause the cellulose of cotton fiber to swell. The swelling occurs in the crystalline region of the fiber. The intermolecular binding force between the cellulose chains remains unchanged. The lattice spacing of cellulose increases, which has no effect on the performance of the final fabric produced. However, as the phosphoric acid content further increases, the swelling phenomenon produced in the amorphous region increases, causing the chemical bonds between the microfibers of cellulose to break. As shown in Comparative Example 4, after the structurally damaged cotton fiber cellulose reacts with the diisocyanate in the raw material and part of the polyterephthalic acid produced by the decomposition of polyester, the mechanical strength of the polymer decreases, and the stress relief rate and breaking strength of the final fabric decrease. The results of Examples 8, 10-12 show that by adjusting the ratio of water to dimethylacetamide in the range of 2-13:3-11, the mechanical properties of the fabric are good; the water content in Comparative Example 5 is too low, and the solubility of cotton fiber in the mixed solvent is poor.

[0065] Examples 14-26

[0066] Different from Example 10, the production process of decomposition liquids 2 and 3 and the production process conditions of the PLA decomposition catalyst are changed, as shown in Table 3.

[0067] Table 3 Production process of decomposition liquid II, III and PLA decomposition catalyst

[0068]

[0069]

[0070] Comparative Example 6

[0071] Different from Example 10, no PLA decomposition catalyst was added.

[0072] Comparative Example 7

[0073] The difference from Example 10 is that 0.4 parts of PLA decomposition catalyst is replaced by 0.4 parts of α-Fe2O3.

[0074] Comparative Example 8

[0075] Different from Example 10, no lactide was added.

[0076] Comparative Example 9

[0077] Different from Example 10, no nanocellulose was added.

[0078] Comparative Example 10

[0079] Unlike Example 10, no composition was added.

[0080] Embodiment 27

[0081] The recycled polylactic acid produced in Examples 10, 14-26 and Comparative Examples 6-10 and the low-temperature spandex fabric were tested for stress relief rate and breaking strength. The test results are shown in Table 4.

[0082] Table 4 Stress relief rate test and breaking strength test results of Examples 10, 14-26 and Comparative Examples 6-10

[0083]

[0084]

[0085] The results of Table 3 and Table 4 show that the stress relief rate of the recycled polylactic acid and low-temperature spandex fabric produced by the present invention is 94.0%-99.2%, and the breaking strength is 97.5-107.4g. The results of Examples 10, 14 and 15 show that as the amount of PLA decomposition catalyst increases, the stress relief rate and breaking strength overall show a trend of first increasing and then decreasing. This is because the synthesized catalyst has the ability to decompose polylactic acid fibers under ultraviolet light irradiation; as shown in Example 11, the amount of PLA decomposition catalyst is too high, and the stress relief rate and breaking strength are reduced instead. The high amount of catalyst will produce excessive decomposition of polylactic acid, and at the same time produce diastereoisomers, cyclic oligomers, carbon monoxide and carbon dioxide and other substances, thereby reducing the content of the effective component lactide, which is not conducive to improving the mechanical properties of the fabric. The results of Examples 14, 16-18 show that by adjusting the amount of α-Fe2O3 and tungsten dioxide in the production process of the PLA decomposition catalyst, the efficiency of catalyzing the decomposition of polylactic acid into lactide is improved. Under the irradiation of ultraviolet light, the PLA decomposition catalyst generates electron-hole pairs, and then generates photogenerated electrons. The electrons overflow to the surface of the catalyst and attack the polylactic acid molecules to achieve the decomposition of the polylactic acid. The tungsten dioxide and α-Fe2O3 simultaneously loaded on titanium dioxide have the best catalytic decomposition effect under the conditions of Example 17, and do not affect the subsequent lactide ring-opening polymerization process. Finally, the stress relief rate and breaking strength of the fabric are improved. The results of Examples 17 and 19-21 show that as the UV irradiation time increases, the stress relief rate increases and then tends to stabilize, and the breaking strength gradually decreases. As the irradiation time increases, the catalyst has achieved the best catalytic effect. As time continues to increase, the irradiation of ultraviolet light destroys the molecular structure of lactide, cotton fiber and spandex in the decomposition liquid 2, the brittleness of the fabric increases, and the breaking strength decreases; Comparative Example 6 does not add a PLA decomposition catalyst, polylactic acid cannot be decomposed, and cannot react chemically with other components. The compatibility of the fabric components is poor, and the stress relief rate and breaking strength decrease. Comparative Example 7 is replaced with an equal amount of α-Fe2O3, and the fabric performance is reduced compared with Examples 10 and 14-26. The results of Examples 19, 22-26 show that by reasonably adjusting the addition amounts of lactide, nanocellulose and the composition, the stress relief rate and breaking strength of the recycled polylactic acid and low-temperature spandex fabrics are improved, among which the best effect is achieved under the conditions of Example 24. On the one hand, the addition of the composition complements the spandex raw materials and improves the elasticity and stress relief rate of the fabric. On the other hand, the isocyanate in the composition polymerizes with nanofibers and open-ring products of lactide and other substances, thereby connecting the polylactic acid and nanofibers that originally had poor elasticity. The three-dimensional network structure formed by the synergistic formation of the substances improves the breaking strength and stress relief rate of the fabric. The results of Comparative Examples 8-10 show that the lack of one of the three types of substances will directly reduce the stress relief rate and breaking strength of the fabric.

[0086] Examples 28-37

[0087] Different from Example 24, the preparation process conditions of S4 and S5 are changed, as shown in Table 5.

[0088] Table 5 Production process of S4 and S5

[0089]

[0090]

[0091] Comparative Example 11

[0092] The difference from Example 24 is that the lactide ring-opening catalyst is replaced by zinc 2-ethylhexanoate.

[0093] Comparative Example 12

[0094] Different from Example 24, no epoxy compound was added.

[0095] Comparative Example 13

[0096] The difference from Example 24 is that the amount of lactide ring-opening catalyst used in S4 is 0.03 parts, and the amount of lactide ring-opening catalyst used in S5 is 0 parts.

[0097] Comparative Example 14

[0098] The difference from Example 24 is that the amount of lactide ring-opening catalyst used in S4 is 0 part, and the amount of lactide ring-opening catalyst used in S5 is 0.03 part.

[0099] Comparative Example 15

[0100] Different from Example 24, the reaction temperature of S4 is 170°C.

[0101] Embodiment 38

[0102] The fabrics produced in Examples 24, 28-37 and Comparative Examples 11-15 were tested for heat resistance. The test method was as follows: the fabrics were placed in an environment of 140°C for 2 hours, and then the changes in stress relief rate and breaking strength were compared. The heat resistance test results are shown in Table 6.

[0103] Table 6 Test results of heat resistance of Examples 24, 28-37 and Comparative Examples 11-15

[0104]

[0105] The results of Tables 5 and 6 show that the recycled polylactic acid and low-temperature spandex fabrics produced by the present invention have a 300% stress relief rate of 92.1%-99.7% and a breaking strength of 96.0-109.3g without being treated at 140°C. After being treated at 140°C, the 300% stress relief rate is 83.4%-97.7% and the breaking strength is 90.7-108.0g. The results of Examples 24, 28-30 show that by changing the type of ethylene oxide, the stress relief rate and breaking strength of the fabrics treated and not treated at 140°C are changed. The epoxy compound is added during the ring-opening decomposition process of lactide. The epoxy compound is ring-opened under high temperature, vacuum and the presence of a catalyst to obtain a compound containing hydroxyl groups. The hydroxyl compound and the partially opened lactide undergo polymerization, which promotes the ring-opening process of lactide and introduces other structural groups in the epoxy compound into it. The stress relief rate and breaking strength of the fabrics treated and not treated at 140°C under the conditions of Example 28 are lower than those of Examples 24, 29 and 30. This is because the structural group introduced into the ring-opening lactide in Example 28 is a short-chain alkane, and the fabric is prone to shrinkage after treatment at 140°C. Example 30 uses epoxyisoquinoline as the epoxy compound, and the reduction in 300% stress relief rate and breaking strength after treatment at 140°C is small, and the fabric has good temperature resistance. Comparative Example 12 does not add epoxy compounds, and the temperature resistance of the fabric decreases. The results of Examples 30 and 31 show that as the amount of 1-(chloro-1-pyrrolidinylmethylene)pyrrolidine tetrafluoroborate is further increased, the temperature resistance is improved. The results of Examples 31 and 32 show that when the amounts of the raw materials 1-(chloro-1-pyrrolidinylmethylene) pyrrolidine tetrafluoroborate and zinc trifluoromethanesulfonate used in the preparation process of the lactide ring-opening catalyst are 3.0 and 0.1 parts respectively, the heat resistance effect is the best. This is because by using 1-(chloro-1-pyrrolidinylmethylene) pyrrolidine tetrafluoroborate as a reaction raw material and reacting with 1,2-cyclohexanediamine, one molecule of 1,2-cyclohexanediamine is connected with two molecules of 1-(chloro-1-pyrrolidinylmethylene) pyrrolidine tetrafluoroborate to obtain a guanidine ligand, and the guanidine ligand is then reacted with zinc trifluoromethanesulfonate to obtain a zinc-centered ligand catalyst, which promotes the ring-opening polymerization reaction of lactide. The amount of raw materials used in the catalyst synthesis is reasonably adjusted, so that the cross-linking degree between the ring-opening lactide and each component is improved, the temperature resistance is improved, and the introduced fluorine atoms and boron atoms also improve the temperature resistance of the fabric. In comparative example 11, the lactide ring-opening catalyst was replaced with zinc 2-ethylhexanoate, and the temperature resistance of the fabric was lower than that of examples 24, 28-37. The results of examples 32-35 showed that the temperature and time of the reaction in the S4 process were reasonably adjusted, and the 300% stress relief rate and breaking strength before and after treatment at 140°C under the conditions of example 33 were the highest.The temperature of comparative example 15 is too high, and the stress relief rate and breaking strength of the fabric decrease. This is because part of the lactide ring-opening catalyst is added first. Under vacuum and high reaction temperature, the reaction temperature is too high and the reaction time is too long, which will have two adverse effects. First, the lactide ring-opening polymerization process is too fast, and it is impossible to achieve reaction and polymerization with other components. On the other hand, the high temperature destroys the molecular structure of polylactic acid and nanocellulose in the decomposition liquid three, so the heat resistance of the fabric decreases. Therefore, it is necessary to control the reaction temperature and time of the S4 process within a reasonable range. The results of Examples 33 and 36 show that the lactide ring-opening catalyst is added in stages in the S4 and S5 processes, and the resulting fabric has good heat resistance; Comparative Examples 13 and 14 do not add the lactide ring-opening catalyst in stages, and the lactide ring-opening polymerization is too fast or cannot achieve complete ring opening, and the heat resistance of the fabric decreases. The results of Examples 36 and 37 show that the reaction temperature and time of the S5 process are reasonably adjusted, the components react completely, and the stress relief rate and breaking strength of the fabric are improved.

[0106] Examples 39-50

[0107] Different from Example 36, the types and proportions of the composition in S5 and the types and proportions of the processing aids in S6 are changed, as shown in Table 7. The three substances in S5 are vitamin B12, chain extender and isocyanate. The three substances in S6 are humectant, dyeing aid and desizing agent.

[0108] Table 7 Types and proportions of the composition and types and proportions of the processing aids in S6

[0109]

[0110]

[0111] Comparative Example 16

[0112] Different from Example 36, vitamin B12 is not added to the composition of S5, and the ratio of chain extender to isocyanate is 2:1.

[0113] Comparative Example 17

[0114] Different from Example 36, only betaine is added as the processing aid in S6.

[0115] Comparative Example 18

[0116] Different from Example 36, the processing aid of S6 is only sodium cocoyl glycinate.

[0117] Comparative Example 19

[0118] Different from Example 36, no auxiliary dyeing agent is added to the processing aid of S6.

[0119] Comparative Example 20

[0120] Different from Example 36, no desizing agent was added to the processing aid of S6.

[0121] Embodiment 51

[0122] The dye uptake and color fastness of the recycled polylactic acid and low-temperature spandex fabrics produced in Examples 36, 39-50 and Comparative Examples 16-20 were tested, wherein the dye uptake was carried out according to GB / T 23976.1-2009 "Dye uptake rate curve determination method for dye uptake rate", and the color fastness was carried out according to the test method of GB / T 3922-2013 "Textiles-tests for color fastness-color fastness to perspiration (ISO 105-E04:2013.MOD)". The final test results are shown in Table 8 and Figure 1 shown.

[0123] Table 8 Dyeing rate and color fastness results of Examples 36, 39-50 and Comparative Examples 16-19

[0124] Dyeing rate (%) Color fastness (grade) Embodiment 36 90.1 4.0 Embodiment 39 91.4 4.2 Embodiment 40 89.7 4.0 Embodiment 41 86.9 3.8 Embodiment 42 91.8 4.2 Embodiment 43 91.0 4.1 Embodiment 44 90.5 4.1 Embodiment 45 91.5 4.2 Embodiment 46 91.8 4.3 Embodiment 47 92.2 4.3 Embodiment 48 92.0 4.3 Embodiment 49 92.5 4.4 Embodiment 50 92.0 4.2 Comparative Example 16 73.6 3.2 Comparative Example 17 81.3 3.6 Comparative Example 18 85.0 3.8 Comparative Example 19 70.5 3.0 Comparative Example 20 74.6 3.3

[0125] As shown in Table 7 and Table 8, the dyeing rate of the recycled polylactic acid and low-temperature spandex fabric produced by the present invention is 86.9%-92.5%, and the color fastness grade is 3.8-4.4. Figure 1The results of Examples 36, 39-41 show that by adjusting the type of isocyanate added to S5, the dyeing rate and color fastness change, the added isocyanate reacts with vitamin B12, the decomposition product of the spandex raw material and the hydroxyl group of the nanofiber, and the fabric dyeing rate and color fastness obtained under the conditions of Example 39 are the highest. The results of Examples 39, 42-44 show that by reasonably adjusting the proportion of vitamin B12, chain extender and isocyanate, the dyeing rate and color fastness are improved, the tertiary amine structural group in vitamin B12 can participate in the reaction as a nucleophilic reagent, and provide electrons to the cationic dye through the nitrogen atom therein, which promotes the firmness of the dye and the fabric. The dosage is reasonably adjusted so that the three substances are fused into the system with a reasonable hard segment and soft segment ratio. Comparative Example 12 does not add vitamin B12, and the dyeing rate and color fastness are lower than those of the embodiment. The results of Examples 42, 45 and 46 show that the dyeing rate and color fastness change by adjusting the ratio of the wetting agent, the dyeing aid and the desizing agent in S6. The wetting agent has a maintaining effect. The wetting agent 1 is an amphoteric surfactant, and the wetting agent 2 is an anionic surfactant. The two interact with each other to improve the adhesion and color fastness of the cationic dye to the fabric. The sulfonate anion in the coloring aid further promotes the dyeing effect of the cationic dye on the fabric. By adding the desizing agent, the dyeing rate and color fastness are improved. Since the weaving process is prone to breakage, wheat starch is added to improve the toughness of spinning, but its presence will affect the wetting and penetration of the cationic dye on the fiber in the spinning. Therefore, sodium carbonate is added as a desizing agent, and then dyeing is performed to minimize the interference of other components on the dyeing process, and the dyeing rate and color fastness are improved. The results of Examples 46-48 show that by adjusting the type and number ratio of the wetting agent, the dyeing rate reaches the highest under the conditions of Example 47, and the color fastness is high. The results of Examples 47, 49 and 50 show that by changing the type of auxiliary dyeing agent, Example 49 has the highest dye uptake and color fastness, because when the sulfonate radical and the sodium ion are the same, the shorter the side chain, the more conducive it is for the dye to dye the fabric. The results of Comparative Examples 18-20 show that the lack of any one of the substances in the processing aid will directly lead to a decrease in dye uptake and color fastness. The substances in the composition and the processing aid work synergistically to improve the dye uptake and color fastness of the fabric.

[0126] Examples 52-58

[0127] Different from Example 49, the melting temperature, the mass ratio of the first processing aid, the mass ratio of the second processing aid, the proportion of the substances in the finishing agent and the heating program during the dyeing process in S6 are changed, as shown in Table 9.

[0128] Table 9S6 production process conditions

[0129]

[0130]

[0131] Embodiment 58

[0132] Different from Example 49, the rates of the second and third programmed temperature increases were 1.3°C / min.

[0133] Embodiment 59

[0134] Different from Example 49, the first programmed cooling rate is 1.6°C / min.

[0135] Embodiment 60

[0136] Different from Example 49, the rate of the second and third programmed temperature increase was 1.7°C.

[0137] Embodiment 61

[0138] Different from Example 49, the first programmed cooling rate is 2.0°C / min.

[0139] Embodiment 62

[0140] Different from Example 49, the temperature of the second programmed temperature increase is 125°C.

[0141] Embodiment 63

[0142] The difference from Example 49 is that the temperature of the second programmed temperature increase is 130°C.

[0143] Embodiment 64

[0144] Different from Example 49, the temperature of the second programmed temperature increase is 115°C.

[0145] Embodiment 65

[0146] The dyeing rate and color fastness of the recycled polylactic acid produced in Examples 49 and 52-65 and the low-temperature spandex fabric were tested. The final test results are shown in Table 10.

[0147] Table 10 Dye uptake and color fastness results of Examples 49, 52-65

[0148]

[0149]

[0150] The dyeing rate of the recycled polylactic acid and low-temperature spandex fabric produced by the present invention is 88.4%-93.5%, and the color fastness is 4.0-4.5. The results of Table 9 and Table 10 show that in Examples 49, 52-54, as the melting temperature increases, the dyeing rate tends to increase and then decrease. This is because after the melt is mixed with wheat starch, the excessively high melting temperature in a short time will damage the component structure, thereby reducing the dyeing rate and color fastness. The results of Examples 52, 55 and 56 show that by adding the processing aid in batches and adjusting the amount added each time, the dyeing rate and color fastness are high. The moisturizer, dyeing aid and desizing agent in the processing aid have the effect of promoting dyeing and color fixation. By adding them in batches, they play a good color fixation effect again. The results of Examples 56 and 57 show that the ratio of ester quaternary ammonium salt, chitin and silicone polyoxyethylene ether in the truth agent is reasonably adjusted, and the dyeing rate of the fabric is improved. Among them, the ester quaternary ammonium salt has the effect of removing static electricity, thereby reducing the interference of static electricity on the dyeing process, and the silicone polyoxyethylene ether gives the fabric flexibility and promotes the penetration of the dye into the fabric. Chitin has a heat-resistant effect, and the ratio of the three is reasonably adjusted to improve the dyeing rate. The results of Examples 58-64 show that the dyeing rate and color fastness are the highest under the conditions of Example 60. By adjusting the rate of program heating and the rate of cooling, the dye is promoted to penetrate into the fabric under thermal power, and the fastness of the dye and the fabric is improved. At the same time, the maximum temperature of the heating is adjusted to remain in a reasonable range, thereby reducing the impact of excessive temperature on the fabric.

[0151] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A production process of recycled polylactic acid and low-temperature spandex fabric, characterized by: The production process is as follows: S1 fabric recycling; S2, in parts by mass, 20 parts of the crushed fabric and 760-1300 parts of a mixed solvent are mixed at 40-55° C., and a 78%-86% by mass phosphoric acid aqueous solution is added to react to obtain a dissolving solution; the mixed solvent is composed of water and dimethylacetamide in a ratio of 2-13:3-11; S3: adding 0.1-0.4 parts of PLA decomposition catalyst to the dissolving solution, and irradiating with ultraviolet light for 80-102 hours to obtain decomposition solution 1; dissolving 10-12 parts of lactide in 100 parts of dimethylacetamide to obtain a lactide solution; and adding the lactide solution to the decomposition solution 1 to obtain decomposition solution 2; S4 removes water from the decomposition liquid 2 to obtain a treated decomposition liquid 2; The treated decomposition liquid II is mixed with 5 parts of epoxy compound and 0.01-0.03 parts of lactide ring-opening catalyst, reacted at 135-170° C. under vacuum conditions for 15-25 minutes, and then cooled to obtain decomposition liquid III; S5: adding 4-7 parts of nanocellulose and 2-5 parts of the composition to the decomposition liquid 3, and then adding 0.01-0.03 parts of a lactide ring-opening catalyst, reacting at 115-125° C. under vacuum conditions for 60-85 minutes to obtain a melt; the ratio of vitamin B12, triethanolamine and isocyanate in the composition is 6-7:2-3:1-2; S6: Mix the melt with wheat starch and melt the mixture at 140-170°C, and spin the mixture to obtain yarn; add 1 / 3-1 / 4 processing aid to the yarn, and soak the yarn in dye solution after weaving to perform programmed heating, heat preservation and cooling; wherein the second and third programmed heating rates are both 1.3-1.7°C / min; the third programmed heating temperature is 115-130°C; and the first programmed cooling temperature is 1.6-2.0°C / min.

2. The production process of recycled polylactic acid and low-temperature spandex fabric according to claim 1, characterized in that: The production process of the PLA decomposition catalyst in S3 is as follows: 15 parts of tetrabutyl titanate are dissolved in anhydrous ethanol to obtain a tetrabutyl titanate solution; the ratio of the tetrabutyl titanate to the anhydrous ethanol is 1:30; 7 parts of polyethylene glycol with a polymerization degree of 5, 4 parts of nitric acid and 8 parts of water are mixed to obtain a reaction solution 1; 0.10-0.18 parts of α-ferric oxide and 0.05-0.10 parts of tungsten dioxide are added to the anhydrous ethanol in a mortar in small amounts and multiple times to grind to obtain a reaction solution 2; the amount of anhydrous ethanol used is 10 parts; the reaction solution 2 is added to the tetrabutyl titanate solution and stirred, and then the reaction solution 1 is added, stirred at 30°C for 24 hours, dried and ground to obtain a calcined material; the calcined material is put into a tubular furnace, roasted at 450°C for 5 hours, and cooled to obtain the PLA decomposition catalyst.

3. The production process of recycled polylactic acid and low-temperature spandex fabric according to claim 1, characterized in that: The preparation method of the lactide ring-opening catalyst in S4 is as follows: dissolving 2.8-3.0 parts of 1-(chloro-1-pyrrolidinylmethylene) pyrrolidine tetrafluoroborate in 20 parts of acetonitrile to obtain a 1-(chloro-1-pyrrolidinylmethylene) pyrrolidine tetrafluoroborate solution; dissolving 0.9 parts of 1,2-cyclohexanediamine and 2.1 parts of triethylamine in 20 parts of acetonitrile to obtain a mixed solution; slowly adding the 1-(chloro-1-pyrrolidinylmethylene) pyrrolidine tetrafluoroborate solution dropwise to the mixed solution at 0°C, heating to 85°C, refluxing and stirring for 12 hours, and then adding 1.7 parts of sodium hydroxide to obtain a lactide ring-opening catalyst precursor; The lactide ring-opening catalyst precursor is dried under vacuum to remove the organic solvent and the triethylamine, and then 2.3 parts of potassium hydroxide are added, and the mixture is extracted with acetonitrile after stirring, and water is removed with anhydrous sodium acetate and then distilled under reduced pressure to obtain a lactide ring-opening catalyst intermediate; Dissolving 0.1-0.2 parts of zinc trifluoromethanesulfonate in 5 parts of tetrahydrofuran to obtain a zinc trifluoromethanesulfonate solution; dissolving 0.3 parts of the lactide ring-opening catalyst intermediate in 10 parts of tetrahydrofuran to obtain a lactide ring-opening catalyst intermediate solution; Raising the temperature of the lactide ring-opening catalyst intermediate solution to 60° C.; The lactide ring-opening catalyst intermediate solution is dropped into the zinc trifluoromethanesulfonate solution, and the obtained precipitate is filtered, washed with tetrahydrofuran and diethyl ether, and then dried to obtain the lactide ring-opening catalyst.

4. The production process of recycled polylactic acid and low-temperature spandex fabric according to claim 1, characterized in that: The process steps of fabric recycling treatment in S1 are as follows: first, textile fabrics are selected, and textile fabrics that do not meet the requirements are eliminated, including dark-colored fabrics, fabrics with pungent odors, and fabrics with high additive content. The retained fabrics are mixed fabrics of polylactic acid fiber, cotton fiber, polyester fiber and spandex; the mass ratio of polylactic acid fiber, cotton fiber, polyester fiber and spandex in the mixed fabric is 58:34:3:5; the mixed fabric is washed with clean water and then dried, then shredded, and crushed with a pulverizer and opened to obtain pulverized fabric.

5. The production process of recycled polylactic acid and low-temperature spandex fabric according to claim 1, characterized in that: The epoxy compound is one of cyclohexene oxide, ethylene oxide, hydroxyethyl methacrylate and epoxyisoquinoline.

6. The production process of recycled polylactic acid and low-temperature spandex fabric according to claim 1, characterized in that: The temperature of the vacuum condition in S4 is 135-150° C.; the amount of the lactide ring-opening catalyst in S4 and S5 is 0.01-0.02 parts.

7. The production process of recycled polylactic acid and low-temperature spandex fabric according to claim 1, characterized in that: The isocyanate is one of 1,3-bis(1-isocyanato-1-methylethyl)benzene, 4,4'-methylenebis(phenyl isocyanate), toluene-2,4-diisocyanate and isophorone diisocyanate.

8. The production process of recycled polylactic acid and low-temperature spandex fabric according to claim 1, characterized in that: The processing aid contains a moisturizer; the moisturizer consists of betaine and anionic surfactant; the ratio of betaine to anionic surfactant is 1:1-2; the anionic surfactant is one of sodium cocoyl glycinate and sodium lauroyl glutamate.

9. The production process of recycled polylactic acid and low-temperature spandex fabric according to claim 1, characterized in that: The processing aid contains a dyeing aid; the dyeing aid is one of sodium docusate, sodium diisobutyl sulfosuccinate and disodium monoisodecyl sulfosuccinate.

10. The production process of recycled polylactic acid and low-temperature spandex fabric according to claim 1, characterized in that: The ratio of the number of moisturizers, dyeing aids and desizing agents in the processing aids is 3-5:2-5:2-3; the finishing agent is added after the first program cooling in S6; the mass ratio of the ester quaternary ammonium salt, chitosan and silicone polyoxyethylene ether in the finishing agent is 1-3:2:1-5.

Citation Information

Patent Citations

  • Preparation method of easy-to-dye spandex

    CN111118654A

  • Production process of polylactic acid fiber yarn-dyed plain edge fabric

    CN117306065A

  • Dyeing process of cyclically regenerated polylactic acid and environment-friendly low-temperature spandex fabric

    CN118498104A

  • Low-temperature pre-dyeing process for brocade spandex

    CN118958017A